LEADERSHIP CHALLENGES FACING SCHOOL EDUCATORS IN - CHAVALALA, DESMOND (My University, 2011)
Leadership is the cornerstone of success of any organisation. Successful organisations have strong and quality leadership, whereas unsuccessful organisations display poor leadership. Top organisations have shown that where there is better leadership, there is better performance by subordinates. School educators have been faced with a number of challenges since the dawn of democracy in South Africa. Many challenges are the result of traditional practices which have their roots in the apartheid regime. The key challenge school educators are facing is undemocratic leadership, which makes them uncomfortable with the daily execution of their work. The leadership challenge continues to damage the relationship between school educators and their school managers as well as the officials from the Department of Education. The leadership challenge at various schools creates room for finger pointing, lack of trust, suspicious practices and lack of confidence between colleagues. The objective of the research was to investigate the leadership challenges facing school educators in the Manombe circuit of Mopani district in Limpopo province. The study revealed that the leadership problem emanates from the school managers and from poor leadership practices at the district and provincial levels of the Department, which negatively affect performance in the schools. The study revealed that school managers make unilateral decisions, do not motivate their subordinates to perform at their best levels and do not empower their subordinates, and that their negative behaviour is a detrimental example to their subordinates. The study recommends that the school managers in the Manombe circuit undergo training on democratic leadership practices in managing school educators; school managers also need to learn to “tame their tongues”. This training can be carried out in the form of workshops attended by both managers and their subordinates, since good leadership can create a sense of inspiration and hope in the followers. School managers also need to learn to recognise and reward the hard work performed by school educators. They also need to learn to delegate duties to their school educators for them to learn how to do work and be empowered
MM - P&DM
Keywords: Leadership; Education, South Africa